2016
DOI: 10.1371/journal.pntd.0004596
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Multiplex Immunoassay Multi-cruzi for the Serological Confirmation of Chagas Disease

Abstract: BackgroundChagas disease is due to the parasite Trypanosoma cruzi, a protist disseminated by a Triatome vector. This disease is endemic to Latin America and considered by WHO as one of the 17 world’s neglected diseases. In Europe and in North America, imported cases are also detected, due to migration of population outside of the endemic region. Diagnosis of T. cruzi infection is usually made indirectly by the detection of specific antibodies to T. cruzi antigens. Following initial diagnostic evaluation or scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 21 publications
(23 reference statements)
1
36
0
7
Order By: Relevance
“…The assay presented in this study is an extended version of the MultiCruzi confirmatory assay previously described [ 26 ]. We used the sciFLEXARRAYER system (SCIENION, Germany) to print fifteen T .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay presented in this study is an extended version of the MultiCruzi confirmatory assay previously described [ 26 ]. We used the sciFLEXARRAYER system (SCIENION, Germany) to print fifteen T .…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the study we present in this manuscript was to characterize serological profiles of T . cruzi -infected patients on an extended version of the MultiCruzi assay [ 26 ]. By measuring diversity of antibodies we sought to identify surrogate antibody biomarker(s) that could be sensitive and specific for monitoring parasite persistence regardless of PCR results.…”
Section: Introductionmentioning
confidence: 99%
“…New generation tests displaying potentially improved accuracy such as the Chemoluminescent Microparticle ImmunoAssay (CMIA) and its improved version, Architect Chagas (both from Abbott Laboratories, Wiesbaden, Germany) (Abras et al, 2016; Praast et al, 2011), or the Multi-cruzi test (InfYnity Biomarkers, Lyon, France) (Granjon et al, 2016) have been recently developed. Confirming the above mentioned trend, both use a large panel of T. cruzi antigens belonging to the 'parental repertoire' -those discovered in the 80's-, which in the case of the Multi-cruzi test is supplemented with TSSA (Trypomastigote Small Surface Antigen (Di Noia et al, 2002)).…”
Section: Diagnostic Applications For Chagas D Isease: Present Knowledgementioning
confidence: 99%
“…Confirming the above mentioned trend, both use a large panel of T. cruzi antigens belonging to the 'parental repertoire' -those discovered in the 80's-, which in the case of the Multi-cruzi test is supplemented with TSSA (Trypomastigote Small Surface Antigen (Di Noia et al, 2002)). Despite the virtual lack of antigen innovation, these tests incorporate a large degree of automation and highly sensitive detection systems (Abras et al, 2016) or major technical improvements, such as a multiplexed printing method inside ELISA microplates (Granjon et al, 2016). …”
Section: Diagnostic Applications For Chagas D Isease: Present Knowledgementioning
confidence: 99%
“…cruzi immunodominant antigens [ 14 ]. However, several studies showed that the use of single antigens in an assay did not confer the sensitivity required for a diagnostic test [ 14 , 15 ], which prompted the development of tests based on combinations of antigens[ 16 , 17 ], some of which were evaluated in multicenter trials and are commercially available [ 18 20 ]. Synthetic peptides are advantageous for diagnostic applications because they are: i) well defined (ease of quality control), ii) easily produced in large amounts, ii) highly pure and often cost-saving if compared to the production of natural or recombinant antigens in vitro [ 21 ]; and iv) also chemically stable (can be stored lyophilized or dessicated and tend to be stable for several years).…”
Section: Introductionmentioning
confidence: 99%